Immediate challenges faced by the quantum computing in time series analysis - Kussainov, A.S.; Karimova, A.T.; Kussainov, S.G.; Pya, N.Y. (Хабаршы. Физика сериясы, 2013)
We considered a few aspects of quantum computing in connection with the time series analysis. Quantum Fourier Transform was selected as a test example due to its important practical value in spectral analysis, the easiness of implementation and its generic nature with respect to many other quantum algorithms. The obvious drawbacks have been identified preventing the straightforward application of Quantum Fourier Transform to the evolving times series. The limited available register size of a quantum computer may be an issue at the data postprocessing stage, but carry significant practical value if included into the data acquisition stage. The analyzed qubit by qubit procedure is favoring the way most of the time series are acquired, which is one at a time. This procedure should be necessarily considered with the decoherence issue for the big quantum systems and long evolution times.